WISATA KULINER HALAL: SUATU TINJAUAN STRATEGIS PEMASARAN DIGITAL TERHADAP PENINGKATAN KINERJA UMKM - putu hari kurniawan (Jurnal Dinamika Ekonomi & Bisnis, 2019)
This study aims to provide stimulants to leading sectors contributing the state budget non-oil and gas sector. So far, tourism has an extraordinary strategic function in terms of food security and job creation for the community. This brings fresh air to the home industry which is the support of the country's economy, how not 65% of the economic contribution in Indonesia is contributed by SMEs based on home industries. Batam is a special economic zone that has tremendous potential in tourism development. The strategic location close to the economic center of ASEAN, namely Singapore, provides benefits for tourism development, currently especially related to culinary tourism. Culinary and tourism is an identity culture to introduce the potential of an area to the outside community. In connection with this study, the researchers examined the existence of digital marketing as SMEs accommodation in promoting halal culinary products through social media, search engine marketing, and online websites. This study took a sample of consumers who bought halal food for UMKM production in Batam amounting to 160 respondents where proportional sampling method was used in the field application. This study uses the Structure Equation Model (SEM) analysis to easily reveal problems that cannot be answered in previous studies.